2015
DOI: 10.1088/0964-1726/24/5/055009
|View full text |Cite
|
Sign up to set email alerts
|

The electrical breakdown strength of pre-stretched elastomers, with and without sample volume conservation

Abstract: In practice, the electrical breakdown strength of dielectric electroactive polymers (DEAPs) determines the upper limit for transduction. During DEAP actuation, the thickness of the elastomer decreases, and thus the electrical field increases and the breakdown process is determined by a coupled electro-mechanical failure mechanism. A thorough understanding of the mechanisms behind the electro-mechanical breakdown process is required for developing reliable transducers. In this study, two experimental configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 27 publications
0
55
0
Order By: Relevance
“…Table 1 in SI), as breakdown strengths were proved previously to be strongly dependent on the thicknesses of elastomeric films [37], i.e. the thicker PDMS films show low breakdown strength compared to the thin films, due to the increased volume -and thus larger number of defects.…”
Section: Breakdown Strengthmentioning
confidence: 66%
See 2 more Smart Citations
“…Table 1 in SI), as breakdown strengths were proved previously to be strongly dependent on the thicknesses of elastomeric films [37], i.e. the thicker PDMS films show low breakdown strength compared to the thin films, due to the increased volume -and thus larger number of defects.…”
Section: Breakdown Strengthmentioning
confidence: 66%
“…Since the film thickness of silicone elastomers has been shown to influence strongly electrical breakdown strengths [37] and mechanical properties [39], two thicknesses for each film were investigated, i.e. each elastomer formulation was tested in four configurations at each timespan (thick or thin/60% or 120% prestretch), while for the breakdown strength measurements another two configurations were utilised (either non-stretched or stretched to the utilized pre-stretch during the measurement).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32,33] The fitted data is shown in Table 2. For the elastomers the XLR is by far the best performing elastomer with respect to electrical reliability.…”
Section: Breakdown Strengthmentioning
confidence: 99%
“…For thicker films the removal of the excessive heat is slower than for thinner films, which subsequently will decrease breakdown strength as conductivity increases in line with increased temperature [27] . Zakaria et al [27] measured breakdown strength for samples as single films with various thicknesses as well as samples consisting of multiple layers and showed that breakdown strengths of thicker single films decreased by 43% and the multiple layer samples decreased by 31%. In comparison, the plasma-treated films in this study decreased by only 6% in breakdown strength, which…”
Section: Electrical Breakdown Strengthmentioning
confidence: 99%